2013
DOI: 10.1586/14737140.2014.864562
|View full text |Cite
|
Sign up to set email alerts
|

Temsirolimus for advanced renal cell carcinoma

Abstract: Renal cell carcinomas (RCCs) represent one of the ten leading cancer entities with an increasing incidence especially in the western world. Unfortunately, about 25% of the patients develop metastatic RCC (mRCC) associated with a most unfavorable prognosis. In the recent years, various new agents targeting VEGF or VEGF receptor (VEGFR) or the mTOR pathway have been approved for the treatment of mRCC with significant prolongation of progression-free survival and, in part, of overall survival (OS). Targeting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 87 publications
0
13
0
1
Order By: Relevance
“…Regarding different risk subgroups, ASPEN especially indicated a benefit for VEGF-TKI therapy in patients with good or intermediate risk according to MSKCC criteria (PFS 14 vs. 5.7 months in good risk and 6.5 vs. 4.9 months in intermediate risk patients) compared to everolimus. However high-risk patients according to MSKCC criteria showed a better PFS with everolimus (4.0 vs. 6.1 months, HR 0.3) [9]. Taken together, the three studies support a superiority of SUN to mTOR inhibitors as everolimus or TEM in nccRCC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding different risk subgroups, ASPEN especially indicated a benefit for VEGF-TKI therapy in patients with good or intermediate risk according to MSKCC criteria (PFS 14 vs. 5.7 months in good risk and 6.5 vs. 4.9 months in intermediate risk patients) compared to everolimus. However high-risk patients according to MSKCC criteria showed a better PFS with everolimus (4.0 vs. 6.1 months, HR 0.3) [9]. Taken together, the three studies support a superiority of SUN to mTOR inhibitors as everolimus or TEM in nccRCC.…”
Section: Discussionmentioning
confidence: 94%
“…Since nccRCC are excluded from most kidney cancer studies, their optimal treatment is yet not defined. Reports on mTOR inhibitors in RCC have proven a benefit for TEM compared to interferon-α (IFN) [9, 13]. The subgroup analysis of the ARCC study showed a comparable mOS for ccRCC and nccRCC patients receiving TEM, whereas nccRCC patients with IFN had a significantly shorter mOS and a lower ORR than nccRCC patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Zu einer deutlichen Verbesserung der Prognose (verlängertes progressionsfreies Überleben) kam es allerdings erst mit der Etablierung von anti-angiogenetisch wirksamen Tyrosinkinase- sowie mTOR-Inhibitoren im Therapiealgorithmus des metastasierten RCC [38,39,40]. Stratifiziert nach den Risiken für eine günstige, mittlere bzw.…”
Section: Immunonkologie Beim Rcc - Ein Revival Mit Durchbruch?lothar unclassified
“…3 However, due to dose-limiting side effects, the effective concentration of TEM in target tissues is not high enough, and systemic administration has considerable toxic and side effects, thereby affecting the prognosis of RCC. 4 As a result, safer and more effective targeted therapies continue to be demanded in clinical treatment to increase the effective drug concentration in specific target tissues, thereby improving the treatment efficacy and reducing side effects. The targeted drug delivery system (TDDS) is a possible approach to solve this problem.…”
Section: Introductionmentioning
confidence: 99%